Cytotoxic, anti-proliferative, and apoptotic evaluation of Ramalina sinensis (Ascomycota, Lecanoromycetes), lichenized fungus on oral squamous cell carcinoma cell line; in-vitro study - Maryam Koopaie; Hanieh Karimi; Mohammad Sohrabi; Hooman Norouzi (BMC, 2023)
Abstract Background Scientists and medical professionals are actively striving to improve the efficacy of treatment methods for oral squamous cell carcinoma (OSCC), the most frequently occurring cancer within the oral cavity, by exploring the potential of natural products. The active pharmacological compounds found in lichenized fungi have shown potential for aiding in cancer treatment. Recent research aims to evaluate the impact of the lichenized fungus Ramalina sinensis (R. sinensis) on the cell viability and apoptosis of OSCC cell lines, considering the anti-inflammatory and anti-cancer capabilities of lichens. Methods Ramalina sinensis (Ascomycota, Lecanoromycetes) was selected for investigation of its effects on a human oral squamous cell carcinoma cell line. Acetone and methanol extracts of R. sinensis on an OSCC cell line (KB cell line, NCBI Code: C152) were investigated. Viability was assessed by MTT assay analysis, and apoptotic cells were measured using flow cytometry analysis. Scratch assay was used to assess cell migration. The chemical composition and metabolic profiling of R. sinensis were investigated. Results The growth and multiplication of KB cells were observed to undergo a gradual but remarkable inhibition when exposed to various concentrations. Specifically, concentrations of 6.25, 12.5, 25, 50, 100, and 200 μg/mL exhibited a significant suppressive effect on the proliferation of KB cells. The inhibition of cell proliferation exhibited a statistically significant difference between the extracts obtained from acetone and methanol. Flow cytometry results show an increase in apoptosis of OSCC cells by acetone extract. R. sinensis exerted a concentration-dependent inhibitory effect on the migration of OSCC cells. The chemical composition of R. sinensis was investigated using liquid chromatography positive ion electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS), and 33 compounds in the acetone and methanol extracts of R. sinensis were detected. Conclusion The findings provide evidence supporting the beneficial effects of R. sinensis extract on inducing apoptosis in OSCC cells and exerting anti-cancer properties.